Problem-Based Learning in Improving Problem-Solving Ability and Interest in Learning Mathematics: An Empirical Study - Nisa’, Khoirotun; Nasrullah, Anton; Hidayat, Amat; Mahuda, Isnaini; Bhat , Ishfaq Ahmad (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
The main challenge in learning mathematics is improving students' problem-solving abilities and strengthening interest in learning. This research focuses on the Problem-Based Learning (PBL) model's influence on students' problem-solving abilities and interest in learning mathematics. This research investigates how PBL can influence the improvement of students' problem-solving abilities and interest in learning mathematics. The method used was an experimental approach with one group following PBL-based learning and a control group using conventional learning. Data was collected through problem-solving ability tests and learning interest questionnaires. The research results showed that PBL significantly improved students' problem-solving abilities and resulted in a positive increase in interest in learning mathematics. Conclusion: These findings effectively strengthen students' problem-solving abilities and awaken their interest in mathematics. The implication is the importance of implementing PBL in mathematics learning to create more competent and enthusiastic students to explore the world of mathematics.